AN EXPLORATORY REVIEW OF PHARMCOLOGICAL ACTIVITIES OF NOTCHI KUDINEER- A SIDDHA HERBAL DECOCTION USED IN COVID-19 (International Journal of Ayurveda and Pharma Research, 2021)
COVID-19 Caused by the novel corona virus (SARS-CoV-2), which has already pushed the entire global community to change their priorities towards finding a suitable anti-viral medicine and a vaccine. While most of the countries have started to prescribe vaccines, which show varied levels of efficacy, finding an effective anti-viral medicine against the virus is still in the early stages despite full-fledged research activities at global level. Many countries particularly those having a rich traditional health science background like India and China started to recommend medicines belonging to local health traditions. The public utilization of those medicines also yielded good results in terms of prevention of the viral infection, reducing the severity of disease or/and reducing the number of days required to recover from the disease as perceived and reported by the patients and doctors.In Tamil Nadu, there are more than 80 million populations. Siddha medicine is the most widely used system of traditional medicine. ‘Suram’ is the Tamil word equivalent to the term ‘fever’. Kabasuram (Also known as Aiya suram) is one among the 64 types of fevers mentioned in Siddha symptoms of which are identical to those of COVID-19. “Notchi kudineer”– a Siddha herbal formulation is being used since many centuries for fever and respiratory disorders with remarkable success. This review article attempts to explore the pharmacological evidence in support of the therapeutic usage of “Notchi kudineer” hence justifying its usage in respiratory related illnesses having fever as a main symptom like the current pandemic of COVID-19.